2020
DOI: 10.1002/adfm.202006226
|View full text |Cite
|
Sign up to set email alerts
|

Remote Tuning of Built‐In Magnetoelectric Microenvironment to Promote Bone Regeneration by Modulating Cellular Exposure to Arginylglycylaspartic Acid Peptide

Abstract: Mimicking the endogenous physical microenvironment is a promising strategy for biomaterial‐mediated tissue regeneration. However, precise control of physical cues such as electric/magnetic fields within extracellular environments to facilitate tissue regeneration remains a formidable challenge. Here, remote tuning of the magnetoelectric microenvironment is achieved by a built‐in CoFe2O4/poly(vinylidene fluoridetrifluoroethylene) [P(VDF‐TrFE)] magnetoelectric membrane for effective bone regeneration. The magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…[267] Due to the highly tissue-penetrative and biocompatible, remote, and nonintrusive magnetic stimulation via applying external electromagnetic field was reported to be helpful for bone engineering. [268][269][270] It was found that the mobility of RGD peptide functionalized magnetic nanoparticles was regulated by external magnetic field, thereby affecting vinculin and YAP functions. In contrast to RGD with high mobility, the confined RGD promoted osteogenic differentiation of MSCs.…”
Section: Cell Differentiationmentioning
confidence: 99%
“…[267] Due to the highly tissue-penetrative and biocompatible, remote, and nonintrusive magnetic stimulation via applying external electromagnetic field was reported to be helpful for bone engineering. [268][269][270] It was found that the mobility of RGD peptide functionalized magnetic nanoparticles was regulated by external magnetic field, thereby affecting vinculin and YAP functions. In contrast to RGD with high mobility, the confined RGD promoted osteogenic differentiation of MSCs.…”
Section: Cell Differentiationmentioning
confidence: 99%
“…As a non-invasive and convenient treatment tool, magnetic fields have started to be applied in tissue engineering and repair. 9,10 At present, there are four main types of magnetic field: pulsed electromagnetic fields, static magnetic fields (SMF), rotating magnetic fields, and alternating electromagnetic fields. 11 In this work, a SMF was selected as a tool to assist injury healing.…”
Section: Introductionmentioning
confidence: 99%
“…15 The National Center for Complementary and Alternative Medicine (NCCAM) does, however, consider the low SMF produced by neodymium and ferrite magnets to be safe, and the scientific community is urged to examine it for therapeutic uses. Relevant studies have shown that SMFs with different intensity (10,50,80, 100 mT) had no effect on the survival rate of mouse embryonic fibroblasts and caused no damage to the cell membrane. 11 Therefore, it is vital to find a solution to the challenge of how to efficiently stimulate wound healing under lower SMFs.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al constructed a CoFe 2 O 4 /poly(vinylidene fluoride-trifluoroethylene (CFO/P(VDF-TrFE)) electroactive membrane to effectively promote the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) and the regeneration of bone defects in vivo. 2 The reason for piezoelectric biomaterials to promote osteogenesis is believed to provide a suitable endogenous electrophysiological microenvironment. 3 The intrinsic potential intensity, 4 directional structure arrangement 5 and dynamic enhancement on the surface of piezoelectric biomaterials 6 have been used to participate in the construction of a suitable electrophysiological microenvironment to regulate the cell membrane potential, 7 membrane receptor proteins and extracellular matrix, 8 and then mediate cellular osteogenic differentiation behavior.…”
Section: Introductionmentioning
confidence: 99%